2016
DOI: 10.1016/j.inteco.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of sectoral FDI in promoting agricultural production and improving food security

Abstract: The aim of this paper is to examine the effects of foreign direct investments (FDI) on food security for 55 developing countries in a panel framework over the period 1995-2009. There are various measures of food security that can be used. Our first contribution is to build a composite indicator that synthesizes the food indicators used by the Food and AgricultureOrganization to measure the food availability and food utilization. Second, our empirical study is based on a model composed of a food security equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 35 publications
3
67
0
Order By: Relevance
“…The results imply that although foreign direct investment in agriculture in developing countries often has positive effects such as production growth, increase in food availability, improved access to water, and improved sanitary production standards (Ben Slimane et al . ), there could also be negative effects, such as intensification of greenhouse gas emissions, which should not be neglected. The increase of emission intensity, which was shown to be potentially driven inter alia by foreign direct investment inflows, can cause climate externalities and worsen production conditions for all agricultural producers in a host country.…”
Section: Resultsmentioning
confidence: 99%
“…The results imply that although foreign direct investment in agriculture in developing countries often has positive effects such as production growth, increase in food availability, improved access to water, and improved sanitary production standards (Ben Slimane et al . ), there could also be negative effects, such as intensification of greenhouse gas emissions, which should not be neglected. The increase of emission intensity, which was shown to be potentially driven inter alia by foreign direct investment inflows, can cause climate externalities and worsen production conditions for all agricultural producers in a host country.…”
Section: Resultsmentioning
confidence: 99%
“…Wieck et al (2014) [17] found that good governance boosts food security, and good guidelines for investment will contribute and maintain their potential positive influence on economic development and food security. Ben Slimane et al (2016) [13] found that in developing countries the FDI in the agriculture sector supports food security, whereas FDI in the manufacturing and services sectors increases food insecurity. They also found a significant influence of FDI spillover on food security through agricultural production.…”
Section: Agricultural Fdi and Food Securitymentioning
confidence: 99%
“…If we take each indicator of these four indicators separately, we will not get enough information to accurately represent the level of food security. So in Section 4.1, we present a composite indicator that can represent these four indicators together [13]. Figure 1 shows the study sample and levels of composite food security in each country.…”
Section: Data and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies reviewed the problems of increasing the efficiency of planning and forecasting of food security levels and the ways of its provision (Slimane et al, 2015;Moseley, 2015). Moreover, most of the studies present the results of long-term forecasting of food security level for 15-30 years (Van Dijk and Meijerink, 2014;Sreejith and Selvan, 2015;Van Wijk, 2014).…”
Section: Introductionmentioning
confidence: 99%